LOCAL BUDGET AS A FINANCIAL BASIS FOR THE FUNCTIONING OF A TERRITORIAL COMMUNITY - Muravskyi, O. (Sworld-Us Conference proceedings, 2025)
The article examines the essence and significance of the local budget by exploring various aspects. This tool is designed to collect and consolidate funds essential for the operations of local self-government authorities. It aims to finance investment pro